2019
DOI: 10.1007/s11325-019-01835-1
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of obstructive sleep apnoea in women with polycystic ovary syndrome: a systematic review and meta-analysis

Abstract: Background Obesity is a common risk factor for polycystic ovary syndrome (PCOS) and obstructive sleep apnoea (OSA). Both PCOS and OSA are associated with increased risk of type 2 diabetes and cardiovascular disease. Hence, it is important to determine the burden of OSA in women with PCOS. Methods We searched electronic databases (MEDLINE, Embase, CINAHL, PsycINFO, Scopus, Web of Science, OpenGrey, CENTRAL), conference abstracts, and reference lists of relevant articles, up to January 2019. No restriction for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 73 publications
0
25
1
2
Order By: Relevance
“…It is one of the earliest symptoms of obstructive sleep apnea (OSA), which is a complex disorder characterized by repetitive collapse of the pharyngeal airway during sleep [24]. Previous studies have reported that PCOS is associated with a reduction in REM sleep stage time and increased risk for OSA [25][26][27]. Alerted reproductive hormone secretion (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the earliest symptoms of obstructive sleep apnea (OSA), which is a complex disorder characterized by repetitive collapse of the pharyngeal airway during sleep [24]. Previous studies have reported that PCOS is associated with a reduction in REM sleep stage time and increased risk for OSA [25][26][27]. Alerted reproductive hormone secretion (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…57 Furthermore, total white cell count, due to a higher mean neutrophil count, has been found to be significantly greater in women with PCOS when compared to control subjects, despite matching for BMI and insulin resistance. 58,59 Also, as women with obesity and PCOS are at increased risk of developing obstructive sleep apnea (OSA), 60,61 this could be considered a contributing factor. However, while there are multiple studies that have shown a positive association between OSA and the neutrophil to lymphocyte ratio, [62][63][64][65] a value sensitive to physiologic stress, few studies have independently associated OSA with leukocytosis, though it has been noted.…”
Section: Sex Differencesmentioning
confidence: 99%
“…Insulin resistance could be a mediator of metabolic risk in women with PCOS ( 36 ) and this hypothesis should be further evaluated in future studies. Obstructive sleep apnea is associated with higher risk of metabolic disease including HT ( 37 ). The risk of obstructive sleep apnea in normal weight women with PCOS and HT should be further investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%